Degradation effects on dichlorvos by a biocontrol strain, Trichoderma atroviride T23 - Jia-nan SUN; Gao-yue SI; Hong-yi LIU; Ya-qian LI; Xin-hua WANG; Jie CHEN (Journal of Integrative Agriculture, 2023)
Excessive use of organophosphate pesticides (OP), such as dichlorvos, in farming system poses a threat to human health through potential contamination of environment. To date, biodegradation has been prospected most promising approach to eliminate environmental OP residues. Trichoderma species as a biological control microorganism is often exposed to the chemical pesticides applied in environments, so it is necessary to understand the mechanism of degradation of dichlorvos by Trichoderma. In this study, dichlorvos significantly inhibited the growth, sporulation and pigmentation of T. atroviride T23, and the dichlorvos degradation activity of T23 required the initial induction effect of dichlorvos and the culture conditions, including the nutrient and pH values of the medium. Various changed primary and secondary metabolites released from T23 in the presence of dichlorvos were speculated as the energy and antioxidants for the strain itself to tolerate dichlorvos stress. The results showed that T23 could produce a series of enzymes, especially the intracellular enzymes, to degrade dichlorvos. The activities of the intracellular enzyme generated by T23 were differentially changed along time course and especially relied on initial dichlorvos concentration, ammonium sulfate and phosphate added in the medium. In conclusion, some dichlorvos-induced chemical degradation related enzymes of T23 were proved to be involved in the degradation of dichlorvos.